For safeguarding autonomy and citizens' livelihood (Tokyo, 1976)
This report points out the fact that those who benefit from the masses in cites are not identical to those who suffer from the masses in cites- former being corporations and the later individual citizens, and this provides a deep-rooted problem of inequity. The committee has reviewed the current taxation system and submitted reports in four stages concerning the measures to be taken to overcome the lurid picture of cities.
Keywords: Taxation,Finance, public; Tokyo,Tokyo, Japan